Kajian Pelaksanaan Konsep Kampung Tematik di Kampung Hidroponik Kelurahan Tanjung Mas Kota Semarang - Anindya Putri Tamara; Mardwi Rahdriawan (Department of Urban and Regional Planning, Diponegoro University, 2018)
Poverty and poor settlement problems seem inseparable from the urban living space including in Semarang City. One of the Semarang City Government policy innovations to tackle the poverty problems along with urban settlement improvement has been introduced in “GERBANG HEBAT” Program through the formation of kampung tematik (thematic kampong). In line with city development acceleration, thematic kampong needs a comprehensive planning for ensuring its sustainability. Representing a thematic kampong, Hydroponics Kampung in Tanjung Mas Subdistrict is dealing with high poverty level issue. The chosen hydroponics theme has in fact brought forward development complexity in nature against the existing coastal area characteristics. This study aims to examine the implementation of thematic kampong concept as well as the affecting factors towards its ineffectiveness. The research method applies qualitative descriptive data analysis. The results indicate the implementation process of kampong thematic concept in Hydroponics Kampung failed to encourage community empowerment. Hydroponic cultivation to which community welfare improvement sought for has no longer attractive and sustainable. The failure is caused by several factors such as poor kampong improvement planning, poor technical implementation process, the chosen thematic mismatch to the kampong potentials, and the lack of community knowledge and awareness.